Comparative immunohistochemical expression of α-smooth muscle actin in pediatric indirect inguinal hernia and hydrocele - Nugraha, Anshari Dwi; Fikri, Erjan; Delyuzar, Delyuzar (Poltekkes Kemenkes Aceh, 2026)
Background: Indirect inguinal hernia and hydrocele, with reported incidences of up to 4% and 0.0034%, respectively, are consequences of incomplete obliteration of the processus vaginalis. Although both conditions share a similar embryological origin, the molecular mechanisms driving their distinct clinical presentations remain unclear. Alpha-smooth muscle actin (α-SMA) is a widely used marker of myofibroblast activity and tissue remodeling. This study aimed to compare the expression of α-SMA in the processus vaginalis tissue of pediatric patients with indirect inguinal hernia and hydrocele.Methods: An observational analytical study with a cross-sectional approach was conducted at the H. Adam Malik General Hospital between January and June 2025. Processus vaginalis tissues were collected from 50 male pediatric patients (25 hernia and 25 hydrocele cases). The expression of α-SMA was evaluated through semi-quantitative immunohistochemical analysis, assessing both staining intensity and distribution. Data were analyzed using the chi-square test, and p < 0.05 was considered statistically significant.Results: A total of 50 patients were enrolled in the study, with a mean age of 3.98 ± 3.78 y. Statistical analysis revealed a highly significant difference in α-SMA expression between the two groups (p < 0.001). Strong α-SMA expression was observed in 96% of the indirect inguinal hernia group, whereas 96% of the hydrocele group exhibited weak expression (OR 576; 95% CI 34.0–9751.0; p < 0.001). The magnitude of this association indicates a strong relationship between clinical diagnosis and α-SMA expression.Conclusion:α-SMA expression differed significantly between indirect inguinal hernias and hydroceles, with a strong expression predominating in hernia specimens. These findings support an association between indirect inguinal hernias and increased α-SMA–positive stromal elements in the processus vaginalis.